"This is not a game": Immersive aesthetics and collective play - McGonigal, Jane (Melbourne DAC 2003 Streamingworlds Conference, 2003)
The increasing convergence and mobility of digital network technologies have given rise to new, massively-scaled modes of social interaction where the physical and virtual worlds meet. This paper explores one product of these extreme networks, the emergent genre of immersive entertinament, as a potential tool for harnessing collective action. Through an analysis of the structure and rhetoric of immersive games, I explore how immersive aesthetics can generate a new sence of social agency in game players, and how collaborative play techniques can instruct real-world problem-solving.
Keywords: jeux vidéo; multijoueurs; réalité virtuelle